2018
DOI: 10.1101/283812
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genome-wide fitness assessment during diurnal growth reveals an expanded role of the cyanobacterial circadian clock protein KaiA

Abstract: 10

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
29
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(33 citation statements)
references
References 58 publications
3
29
0
Order By: Relevance
“…The RB-TnSeq data for clock histidine kinase genes sasA and cikA had mild negative fitness values, but knockout mutants for either of these genes are still naturally transformable 33 . Loss of the master regulator RpaA has pleiotropic effects, including extreme sensitivity to darkness 34 ; as a result, this locus is so poorly represented in the control library that its loss of competence is not reflected in the pipeline that compares the transformed and untransformed barcodes, as was also true for elucidation of genes required for growth in light-dark cycles 35 . To delve further, we analyzed available circadian and light/dark transcriptomes for S. elongatus 24,36,37 (Supplementary Data 1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The RB-TnSeq data for clock histidine kinase genes sasA and cikA had mild negative fitness values, but knockout mutants for either of these genes are still naturally transformable 33 . Loss of the master regulator RpaA has pleiotropic effects, including extreme sensitivity to darkness 34 ; as a result, this locus is so poorly represented in the control library that its loss of competence is not reflected in the pipeline that compares the transformed and untransformed barcodes, as was also true for elucidation of genes required for growth in light-dark cycles 35 . To delve further, we analyzed available circadian and light/dark transcriptomes for S. elongatus 24,36,37 (Supplementary Data 1).…”
Section: Resultsmentioning
confidence: 99%
“…Then the barcodes were amplified, sequenced and quantified in perl 5v18 using previously developed BarSeq protocols 62 . The barcodes were curated to keep only barcodes located within the middle 80% of each coding sequence, and to keep only the genes represented by at least three barcodes in different positions and with at least 15 T 0 reads across replicates 31,35 . This curation resulted in 82,495 barcodes (also named strains) for the experimental conditions, 90,997 barcodes for the controls, and 99,872 barcodes for the T 0 samples distributed across 1885 genes.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although CikA's role in the clock was discovered through its necessity for phase resetting (Schmitz et al., ), later work showed that it plays a critical role in circadian output as well (Gutu & O'Shea, ). Moreover, CikA competes with KaiA for binding to the KaiB ring in the night‐time complex (Tseng et al., ; Welkie et al., ). Hence, CikA can be considered part of the oscillator itself, affecting circadian period both in vivo and in vitro.…”
Section: Input Oscillator and Outputmentioning
confidence: 99%
“…Hence, CikA can be considered part of the oscillator itself, affecting circadian period both in vivo and in vitro. The circadian output role of CikA depends on a phosphatase activity that is triggered by engagement of CikA with the Kai complex at night (Gutu & O'Shea, ; Welkie et al., ). This activity dephosphorylates a master transcription factor, RpaA, whose rhythmic phosphorylation sets up the oscillation of gene expression that is observable through the entire genome to various extents.…”
Section: Input Oscillator and Outputmentioning
confidence: 99%